Proximal parameters of umbu pulp (Spondias tuberosa Arr. Cam.) commercialized in the municipality of Guanambi, Bahia, Brazil - Silva, Silvania Lopes da; Souza, Ezequiel Victor Nogueira de; Couto, Luzia Almeida; Moreira, Edinilda de Souza; Landim, Lucas Britto; Rusciolelli, Luciano Bertollo; Cafieiro, Cinara Soares Pereira (Brazilian Journal of Science, 2022)
Spondias tuberosa belonging to the Anacardiaceae family, is a fruit species very appreciated by the human and animal population. The main objective of this work was to evaluate the proximate composition of umbu pulp originating in the municipality of Guanambi-Bahia. The study was carried out in the municipality of Guanambi, State of Bahia, Brazil in 2021. The fruit pulp was purchased commercially frozen in local markets. Proximal analyzes were carried out for: moisture, ash, protein, lipids, real crude fiber and carbohydrates, according to the analytical norms of the Instituto Adolfo Lutz. The results obtained showed a high rate of moisture and good fiber contents with 1.95% and carbohydrates with 5.67%. It is concluded that the evaluated parameters of moisture, ashes, proteins, lipids, fibers and carbohydrates for umbu pulp, presented small variations when compared with the values reported by several authors who studied the subject. The results obtained were close to those established by the Brazilian Table of Food Composition.